Kenya launches a Bioenergy Strategy supported by World Agroforestry - CGIAR Research Program on Forests, Trees and Agroforestry (2020)
The African nation is pushing ahead with an ambitious goal to optimize use of bioenergy, supported by World Agroforestry (ICRAF).